Crosslinked alginate/silica/zinc oxide nanocomposite: A sustainable material with antibacterial properties. (March 2018) - Salama, Ahmed; Diab, Mohamed A.; Abou-Zeid, Ragab E.; Aljohani, Hind Abdullah; Shoueir, Kamel Rizq
Abstract: In the current study silica gel was extracted from rice husk as light and cost effective biomaterial followed by incorporation in crosslinked alginate for preparing nontoxic and functionalized nanocomposite material. Alginate/silica hybrid was investigated as a template for zinc oxide formation. Zinc oxide nanoparticles with diameters of ca. 20 nm were homogenously anchored onto alginate/silica hybrid. The antibacterial activity of the composite was evaluated against gram positive (S. aureus) and gram negative (E. coli) bacteria. The current article shows that the alginate/silica/zinc oxide nanocomposite is promising sustainable and disinfection materials to effectively inhibit bacterial. Highlights: New sustainable and bioactive hybrid composed of alginate/silica was prepared. Alginate/silica hybrid contains zinc oxide nanoparticles with diameters of ca. 20 nm was prepared. The antibacterial results presented the current material as promising material for biomedical applications.